Reading-Literacy: Characteristics Of Students In The "Teaching Campus" Program Batch 2 - Lukman Hakim Muhaimin; Christina Monika; Khofifa Romaito Siregar; Dadan Dasari (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
Various gaps exist in every education system. This will impact students' literacy skills, as evidenced by the PISA ranking every year indonesia is still in the lower class. The purpose of this study was to describe the reading literacy ability of the students of SD N 1 Brajan towards the class 2 teaching campus program. This study was qualitative research with a phenomenological design. The subjects taken were fifth-grade students of SD N 1 Brajan for the academic year 2021/2022, with the technique of taking the subject using Snowball Sampling. The time used by the researcher was 30 days at SD N 1 Brajan, Klaten district, Central Java province. The auxiliary instrument used is the class 2 teaching campus program: wall magazines, literacy trees, and literacy tips. The data obtained were drawn using interviews and observations. The validity of the data is required using triangulation methods with inductive data analysis techniques. The results showed that students' reading literacy skills were high, with various characteristics that appeared for each student in each indicator. Hopefully, this research can illustrate that campus teaching activities have a good impact on schools, especially schools with the 3T predicate.